Preventing youth depression: Simulating the impact of parenting interventions. (September 2018) - Lay-Yee, Roy; Milne, Barry J.; Shackleton, Nichola; Chang, Kevin; Davis, Peter
Highlights: We construct a simulation model of the early life course. The model integrates data from empirical sources including meta-analytic estimates. We test potential interventions on parenting behaviors to reduce youth depression. We show socio-economic gradients in effectiveness. We develop and provide a publicly accessible research tool for policy makers. Abstract: Depression is an increasing global problem, and was the leading cause of disability in 2015. Much is known about the factors that give rise to depression, and social inequalities in its prevalence, but less about empirically based interventions that might prevent its occurrence. We focus on the role of maternal parenting factors (that is emotional warmth and harsh discipline) experienced in childhood affecting depression in youth (aged 15–21 years) in New Zealand. We introduce a novel simulational life-course approach. We use estimates from meta-analytic reviews on the effects of maternal parenting factors to drive a simulation model of the early life course. We then mimic possible interventions by testing scenarios based on modifying these key factors and assessing their impact on depression. We find that reduction in depression prevalence is better achieved by altering a combination of rather than single maternal parenting factors, and that the social groups in which youth are structurally embedded (by parental social position) are differentially affected. In the most optimistic scenario, if both lack of emotional warmth and harsh discipline could be completely eliminated in childhood, our model shows that youth depression overall (baseline 7.4%) would be reduced by about a fifth (to 5.8%), while the greatest improvement would accrue to youth who had parents without formal educational qualifications (baseline 11.3%) by nearly a third (to 7.7%). Our findings support the utility of our approach for policy making on population health issues, in this case, indicating maternal parenting interventions that might be effective in preventing youth depression and the social groups that might gain most benefit.